2013
DOI: 10.2139/ssrn.2433796
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Economic, Fiscal, and Financial Shocks in the Evolution of Public Sector Pension Funding

Abstract: Abstract:Many studies have documented the pervasive underfunding of public sector pension plans in the United States in recent years. The deterioration of the funded status of public pension plans coincided with severe fiscal crises that state and local governments experienced in the 2000s. This development has led to a suspicion that state and local governments have decreased employer pension contributions as a backdoor means of running fiscal deficits. In this paper, the authors investigate the extent to whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…If it is the latter, researchers will inaccurately assert that financial stress shifts resources away from pension contributions in situations when, in fact, the contribution actually increases, but just not by as much as the required contribution. The first interpretation is common among pension researchers, but preliminary research shows support for the latter (Triest & Zhao, 2013).…”
Section: Literature Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…If it is the latter, researchers will inaccurately assert that financial stress shifts resources away from pension contributions in situations when, in fact, the contribution actually increases, but just not by as much as the required contribution. The first interpretation is common among pension researchers, but preliminary research shows support for the latter (Triest & Zhao, 2013).…”
Section: Literature Reviewmentioning
confidence: 98%
“…If it is the latter, researchers will inaccurately assert that financial stress shifts resources away from pension contributions in situations when, in fact, the contribution actually increases, but just not by as much as the required contribution. The first interpretation is common among pension researchers, but preliminary research shows support for the latter (Triest & Zhao, 2013). Table 1 illustrates three groups of explanatory variables that are used to measure the effect of political economies on the financial performance of public pensions: (a) political preferences, (b) fiscal stressors and constraints, and (c) administrative professionalism.…”
Section: Measuring the Financial Performance Of Public Pensionsmentioning
confidence: 99%
“…From the budget management standpoint, accumulative pension payment shortfalls are somewhat analogous to the debt that accumulates from operating deficits. Pension benefits are a form of deferred employee compensation, failure to set aside enough funding to cover the pension benefits those employees earned for that year is equivalent to not fully paying the labor cost component of the operating budget with current‐year revenues (Triest & Zhao, 2013; Rauh, 2017). Peng (2004) showed that pension contributions were used as a countercyclical budgetary tool as policymakers lower pension contributions below required levels when faced with budget deficits.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies have evaluated the funding soundness of pension systems by examining pension funding levels, however, this study focuses on the percentage of ADEC paid as a proxy for a government's budgetary decision to meet its pension obligation (St.Clair, 2013; Triest & Zhao, 2013). Since pension funding measures are largely affected by investment earnings, which account for 60%–70% of pension assets (National Association of State Retirement Administrators [NASRA], 2020; Urban Institute, 2017), fiscal conditions and fiscal constraints are more visibly and precisely measured through state pension contributions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A third limitation of the existing research is that it assumes a constant, simultaneous relationship between discount rates and the financial condition of public pensions. All of the studies that regress the financial condition of public pensions on discount rates specify a linear relationship (Mitchell and Hsin ; Mitchell and Smith ; Rich and Zhang ; Triest and Zhao ). Other researchers assume a linear relationship in the way that they attempt to standardize financial conditions across multiple pension systems that have different discount rates and salary growth rates.…”
Section: Introductionmentioning
confidence: 99%